2014
DOI: 10.1007/s00421-014-2933-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypervolemia induced by fluid ingestion at rest: effect of sodium concentration

Abstract: Beverages containing 120 mmol l(-1) Na(+) induce hypervolemia with a minimum incidence of gastrointestinal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…F luids containing sodium have been shown to increase plasma volume greater at rest (22,26,31,32,37) and to maintain plasma volume better during exercise (3,4) than water alone. Given the concerns of some about performance impairment from weight loss during exercise of only 2% body weight, recent guidelines recommend ingestion of sodium with fluids during exercise (1,2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…F luids containing sodium have been shown to increase plasma volume greater at rest (22,26,31,32,37) and to maintain plasma volume better during exercise (3,4) than water alone. Given the concerns of some about performance impairment from weight loss during exercise of only 2% body weight, recent guidelines recommend ingestion of sodium with fluids during exercise (1,2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned study conducted by Fuji et al reported no differences in cumulative urine or plasma volume between 120 mmol/L or 180 mmol/L sodium concentrations, thus denoting that sodium levels higher than 120 mmol/L might not lead to additional benefits in terms of changes in plasma volume [ 193 ]. In a previous study, water and three solutions containing 60, 120, or 180 mmol/L sodium, respectively, were compared [ 194 ]. In trials separated by three days, eight euhydrated males ingested 16–17 mL/kg body weight (≈1 L) of one of the three formulations or water within 60 min, and were followed a total of 150 min under controlled environmental conditions [ 194 ].…”
Section: Impact Of Exercise Timing On Carbohydrate–electrolyte Solutionsmentioning
confidence: 99%
“…In a previous study, water and three solutions containing 60, 120, or 180 mmol/L sodium, respectively, were compared [ 194 ]. In trials separated by three days, eight euhydrated males ingested 16–17 mL/kg body weight (≈1 L) of one of the three formulations or water within 60 min, and were followed a total of 150 min under controlled environmental conditions [ 194 ]. As expected, the 120 and 180 mmol/L solutions were shown to be more effective than the 60 mmol/L solution or water at reducing cumulative urine volume and promoting net fluid balance [ 194 ].…”
Section: Impact Of Exercise Timing On Carbohydrate–electrolyte Solutionsmentioning
confidence: 99%
See 2 more Smart Citations